2005
DOI: 10.1093/ajcn/82.3.575
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum concentrations of 25-hydroxyvitamin D and gingival inflammation

Abstract: Vitamin D may reduce susceptibility to gingival inflammation through its antiinflammatory effects. Gingivitis may be a useful clinical model to evaluate the antiinflammatory effects of vitamin D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
254
4
10

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(285 citation statements)
references
References 45 publications
17
254
4
10
Order By: Relevance
“…Des études ont montré un lien entre l'ostéo-porose, une faible densité de l'os alvéolaire et la perte des dents [82]. À partir de l'analyse de 1 1202 sujets issus de la population NHANES, il existe un lien significatif entre les taux de vitamine D et la perte de l'attachement du périodonte chez les sujets âgés de plus de 50 ans ; comparativement aux sujets qui ont un taux de 25OHD dans le quintile inférieur, la perte de l'attachement du périodonte est significativement moins importante chez les sujets qui ont un taux de 25OHD dans le quintile supérieur (entre 90 et 100 nmol/L) [83,84]. Dans un essai randomisé contre placebo de 3 ans conduit chez 145 sujets (âge moyen 71,5 ans), la supplémentation par 700 UI de vitamine D et 500 mg/j de calcium diminue la perte des dents (OR = 0,4 ; IC 95 % 0,2-0,9) ; les taux de 25OHD augmentant de 71 à 112 nmol/L.…”
Section: Effet De La Vitamine D Sur Le Périodonteunclassified
“…Des études ont montré un lien entre l'ostéo-porose, une faible densité de l'os alvéolaire et la perte des dents [82]. À partir de l'analyse de 1 1202 sujets issus de la population NHANES, il existe un lien significatif entre les taux de vitamine D et la perte de l'attachement du périodonte chez les sujets âgés de plus de 50 ans ; comparativement aux sujets qui ont un taux de 25OHD dans le quintile inférieur, la perte de l'attachement du périodonte est significativement moins importante chez les sujets qui ont un taux de 25OHD dans le quintile supérieur (entre 90 et 100 nmol/L) [83,84]. Dans un essai randomisé contre placebo de 3 ans conduit chez 145 sujets (âge moyen 71,5 ans), la supplémentation par 700 UI de vitamine D et 500 mg/j de calcium diminue la perte des dents (OR = 0,4 ; IC 95 % 0,2-0,9) ; les taux de 25OHD augmentant de 71 à 112 nmol/L.…”
Section: Effet De La Vitamine D Sur Le Périodonteunclassified
“…Vitamin D3 (cholecalciferol) and its active metabolites, 25-hydroxyvitamin D3 (calcidiol) and 1,25-dihydroxyvitamin D3 (calcitriol), have long been known to be important for their direct or indirect effects on the uptake of calcium and phosphorus from the gut and into bone (Weaver and Fleet, 2004), but over the past decade it has become clear that this vitamin also has favorable effects in a number of other health-related areas, including those associated with multiple sclerosis (Munger et al, 2004;VanAmerongen et al, 2004), diabetes (Hypponen et al, 2001), certain forms of cancer (Guy et al, 2004), periodontal disease (Dietrich et al, 2004), fracture prevention (DawsonHughes, 2005), and immune activation (Griffin et al, 2003). Partly as a result of these findings the recommended adequate dietary intakes for vitamin D (Weaver and Fleet, 2004) are under discussion and a number of researchers have suggested that these levels should be higher than is currently the case (Heaney, 2003;Holick, 2004;Vieth, 2004;Weaver and Fleet, 2004;Hollis, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…35 Further primarily epidemiologic evidence of a beneficial effect of vitamin D exists for colon cancer, 36 multiple sclerosis, 37 insulin resistance, 38,39 other cancers, [40][41][42][43] osteoarthritis, 44,45 hypertension, [46][47][48] and periodontal disease. 49 One major source of vitamin D is sun exposure, with an action spectrum peaking in the UVB (290-320 nm) range. Exposing 5% of the uncovered body surface twice a week in summer may be equivalent to an intake of 430 IU of vitamin D per day; however, for a given surface area, a plateau is reached after 20 minutes.…”
Section: Biologic Effects and Sources Of Vitamin Dmentioning
confidence: 99%